KORELASI UNDANG-UNDANG PERLINDUNGAN ANAK NOMOR 35 TAHUN 2014 DENGAN KETEGAASAN GURU DAN EFEKTIVITAS PENDIDIKAN AKHLAK SISWA SMP MA’ARIF NU TUGUMULYO - Muhammad Faizul Amirudin (El-Ghiroh : Jurnal Studi Keislaman, 2017)
he purpose of this research is to know the correlation of Child Protection Law with Teacher's Firmness and effectiveness of Moral Education at Ma'arif Junior High School Tugumulyo. This type of research is a correlation research using quantitative research methods. The place of study was conducted at Ma'arif Junior High School Tugumulyo. The subject of this research is educators or teachers of Ma'arif Junior High School Tugumulyo NU both the civil servants and honorary. The analysis used included quantitative data analysis. Analysis to test the hypothesis used r test before the data tested normality and linearity. Based on the results obtained from quantitative analysis, firstly, there is a significant correlation Child Protection Act No. 35 year 2014 with teacher firmness with the value of correlation coefficient 0.574 larger than r table is 0.444 which means strong correlation and its significance 0.008. secondly, there is no significant correlation of Child Protection Act No. 35 year 2014 with the effectiveness of moral education in SMU Ma'arif NU Tugumulyo. The correlation coefficient value of 0.334 is smaller than r table with the price of 0.444 which means weakness and significance level of 0.150 which is greater than 0.05 means not significant.